Effectiveness of Implementing the Government's Internal Control System in the District - Risnandar, Heri; Maruapey, Muhammad Husein; Iskandar, Abu Bakar; Wahyudin, Cecep (Tinta Emas Institute, 2024)
The urgency of this research is based on the need to ensure that the internal control system runs well to increase accountability, transparency, and performance of local government. This research aims to analyze the effectiveness of the implementation of the government's internal control system in Cisarua District, Bogor Regency. This research uses a qualitative descriptive method with a case study approach. Data was collected through in-depth interviews, observation, and documentation. Data analysis was carried out using triangulation techniques to ensure the validity and reliability of the findings. The research results show that good relationships between leaders and members, clarity of task structure, and appropriate use of technology are key factors that support the effectiveness of internal control. However, research also identifies several inhibiting factors, such as limited human resources, lack of coordination between departments, and budget constraints. The research discussion emphasizes the importance of increasing the number and quality of human resources through continuous recruitment and training, as well as optimizing the use of information technology to automate control processes. In addition, improving coordination and communication between departments and seeking alternative funding sources were also identified as important steps to overcome these inhibiting factors.